Utilization of Online Digital Marketing for Product Development Through Social Media - Yayuk Yuliana; Vera Kristiana; Wan Dian Safina; Slamet Indarjo (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
In today's tight business world competition, all businesses must pay attention to online marketing. One of the problems that emerged during this Community Service activity was that the people of Kelahan Harjosari II, Medan Amplas District did not have the knowledge of how to market their goods digitally, which would enable them to make more of their goods for their family's needs. The aim of this counseling is to help them understand better about digital marketing. MSMEs in Harjosari II Village, Medan Amplas District, are the targets of this community service program. The method of implementing this activity is through presentations and lectures. The result of community service activities is increased knowledge and understanding about online marketing, as shown by the social media selection strategy used for online marketing activities because social media is very popular in Indonesia. Participants can also create marketing content that suits their target market and product type.